Association of Dietary Cholesterol Intake With Risk of Gastric Cancer: A Systematic Review and Meta-Analysis of Observational Studies - Miao, Peng; Guan, Lin (Frontiers in Nutrition, 2021)
Background: Many case-control studies have investigated the association between dietary cholesterol and gastric cancer risk, but their findings are inconsistent. A systematic review and meta-analysis of observational studies were carried out to assess the relationship between dietary cholesterol intake and gastric cancer in adults. Methods: PubMed, Scopus, and Google Scholar were systematically searched to identify articles that evaluated the association of dietary cholesterol with gastric cancer up to May 2021. Pooled odds ratio (ORs) and 95% confidence intervals (CIs) were computed using random-effects models. Dose-response analysis was conducted to explore the shape and strength of association. Results: Fourteen case-control studies with 6490 GC patients and 17793 controls were met inclusion criteria. In the meta-analysis of highest versus lowest dietary cholesterol categories, 35% of increased risk of gastric cancer was observed in relation to cholesterol consumption (Pooled OR: 1.35, 95% CI: 1.29 to 1.62, I2 =70.1%; Pheterogeneity<0.001). Subgroup analysis also showed this positive relationship in population-based case-control studies, those conducted on non-US countries, those with a higher number of cases, high-quality studies, those collected dietary data by interview way, studies not adjusted to H-pylori infection, and studies controlled BMI. Besides, a nonlinear dose-response association also was identified (P=0.03). Conclusion: This study demonstrated that dietary cholesterol intake could significantly augment the risk of gastric cancer in case-control studies. Prospective cohort studies with greater sample size and a high duration of follow-up are required to verify our results.